Dinamika Penguatan Pendidikan Karakter Peserta Didik Sma Kabupaten Lombok Timur - Hairi, Husnul; Badarudin, Badarudin; Mashun, Mashun (Universitas Hamzanwadi, 2024)
Character education is an education of ethics, morals, values, and character, which aims to develop the ability to determine good and bad and apply goodness in life. To realize character education, a foundation is needed as a reference in shaping the character of students. This study aims to analyze how the planning, implementation, and evaluation process on strengthening the character education of students at SMA Negeri 1 Aikmel East Lombok. This research uses a qualitative approach, with a descriptive qualitative type. The research site was at SMA Negeri 1 Aikmel East Lombok, with the subject of the research being the principal and the research informants being the student affairs and teachers. While the data collection technique uses observation, interview and documentation techniques, the data validation technique is carried out by triangulation, namely the triangulation technique of data sources and methods, then the data analysis technique is carried out in several stages, namely data collection, data reduction, data display and conclusions drawing/verifying. The results of this study obtained an overview that: first, planning has been carried out as best as possible starting from the program planning meeting of goal formulation, strategy preparation, policy determination, procedure mapping, and program improvement involving all components of the school, deputy principal for curriculum, student affairs, infrastructure, public relations, treasurer, educators and education staff and school committees.; Second, the implementation of strengthening the character of students runs well through organizing activities and actions focusing on the character values of students; Third, the evaluation of the process of strengthening students' character education through activities to supervise the implementation of activities, reflect, analyze and follow up.